Corporate Managerialism in a Rural Setting: A Contextualized Case Study - Elizabeth Hatton (Journal of Research in Rural Education, 1996)
It is now commonplace to find in Australia two modes of school management deriving from corporate modes of management: devolution ofauthority and responsibility, and strategic or school-development planning. This case study provides an interpretive account of the process of strategic planning in devolved structures in a small, rural primary school in northern New South Wales, Australia. It documents and analyses how the school sets about the process of strategic planning. While student outcomes have been enhanced as a result ofpolicies and programs devised and implemented by staffthrough strategic planning, the case study reveals distinctive difficulties in implementing corporate modes ofmanagement in a working class, racially- and gender-divided, small, rural school.